Navigating the Digital Battlefield: Exploring the Intersection of Digital Media and Fifth-Generation Warfare in Pakistan - Salma, Maaidah; Ahmed, Umair; Warraich, Saqib Khan (Annals of Human and Social Sciences, 2023)
In the 21st century, warfare has evolved into a battle of perception and information, with the internet and social media playing key roles. This includes the spread of fake news, propaganda, and disinformation through platforms like Facebook, WhatsApp, Instagram, and Twitter. The present study delves into the intersection of digital media and fifth-generation warfare, scrutinizing their collective impact on Pakistan's information culture. Contemporary warfare strategies extend beyond kinetic methods, encompassing non-kinetic approaches that manipulate ideologies and perceptions. In the context of Pakistan, the exploitation of ideological fault lines through digital media has emerged as a potent destabilizing force. This study identifies vulnerabilities within Pakistan's information culture and elucidates the factors influencing its susceptibility to manipulation. A qualitative exploration of the subject is undertaken through in-depth interviews with experts possessing profound insights into the matter. The resultant thematic data analysis reveals a significant gap in public awareness, leading to inadvertent contributions to the erosion of Pakistan's information culture. Central concerns center around the misuse of the right to freedom of expression, the prevalence of unchecked news dissemination, and the prioritization of personal beliefs over national security imperatives. Notably, these challenges are exacerbated by the pervasive influence of digital media platforms. This paper proposes ideological and administrative reforms in response to these challenges. These measures aim to fortify Pakistan's defenses against the insidious threats of fifth-generation warfare. By addressing the root causes that allow disinformation and manipulation to thrive, these reforms seek to rejuvenate the integrity and resilience of Pakistan's information culture.